2016
DOI: 10.1111/and.12627
|View full text |Cite
|
Sign up to set email alerts
|

Sperm mitochondrial DNA deletion in Iranian infertiles with asthenozoospermia

Abstract: Asthenozoospermia is an important cause of male infertility. The mutations in sperm mitochondrial DNA (mtDNA) result in either functionless or malfunctioning some proteins, subsequently affecting sperm motility leading to asthenozoospermia. The purpose of this study was to investigate sperm mtDNA 4,977-bp deletion in infertile men with low sperm motility/immotile spermatozoa compared to healthy subjects with high sperm motility. Semen samples of 256 asthenozoospermic infertiles and 200 controls from northern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Several studies have suggested that sperm motility and male fertility can be reduced by mtDNA mutations (Baklouti-Gargouri et al, 2013;Zhou and Xie, 2017). Other investigations confirmed the correlation between male infertility and mtDNA deletions Hosseinzadeh Colagar and Karimi, 2014;Chari et al, 2015;Bahrehmand Namaghi and Vaziri, 2017). Talebi et al (2018) recorded deletions of approximately 4977 and 7599 bp in the mtDNA of infertile men.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have suggested that sperm motility and male fertility can be reduced by mtDNA mutations (Baklouti-Gargouri et al, 2013;Zhou and Xie, 2017). Other investigations confirmed the correlation between male infertility and mtDNA deletions Hosseinzadeh Colagar and Karimi, 2014;Chari et al, 2015;Bahrehmand Namaghi and Vaziri, 2017). Talebi et al (2018) recorded deletions of approximately 4977 and 7599 bp in the mtDNA of infertile men.…”
Section: Introductionmentioning
confidence: 90%
“…If the mtDNA 4977 deletion occurs during spermatogenesis and/or spermiogenesis, the mature spermatozoa are endowed with dysfunctional mitochondria, which can act as a source of ROS. Interestingly, mtDNA 4977 has been recorded in the spermatozoa of infertile males with asthenozoospermia and oligoasthenozoospermia [148,149]. An alternative large-scale mtDNA deletion comprising 7436 bp (mtDNA 7436 ) has also been reported in low-motility human spermatozoa [150].…”
Section: Sperm Dna Modificationsmentioning
confidence: 99%
“…33 Several studies have also confirmed the significantly higher occurrence of the common mtDNA 4977-bp deletion in patients with asthenozoospermia and oligoasthenoteratozoospermia compared with healthy individuals. 23,26,40 In contradiction with these results, no statistically significant correlation was revealed between the occurrence of the "common" deletion alone and sperm motility classification in percoll fractions 30 or semen quality. 25 In this study, our PCR analysis clearly demonstrated the presence of three large-scale mtDNA deletions of 4.8, 4.9 and 7.4 kb in spermatozoa with different motilities in both AT infertile patients and the normozoospermic group.…”
Section: Discussionmentioning
confidence: 71%